Analysis of Satisfaction with Outpatient Medical Record Provision Services Based on the CSI Method at Majalengka Regional Hospital in 2024: Analisis Kepuasan Layanan Penyediaan Rekam Medis Rawat Jalan Berdasarkan Metode CSI di RSUD Majalengka Tahun 2024 - Sugandi, Hana Luthfiyah; Subianto, Totok; Suhartini; Elfi (Jurnal Rekam Medis dan Informasi Kesehatan, 2024)
Based on the Decree of the Minister of Health of the Republic of Indonesia (2008) regarding Minimum Service Standards for Hospitals, the time for providing medical records for outpatients is less than 10 minutes. However, in reality the length of time for distribution of outpatient medical records often exceeds the specified limits. This can affect the quality of health services and staff satisfaction with medical records services, especially in outpatient medical records services. The aim of this research is to examine the satisfaction of outpatient polyclinic officers regarding the provision of outpatient medical records services at Majalengka Regional Hospital in 2024. The method used is quantitative descriptive cross-sectional, with a total sample of 40 outpatient polyclinic officers. The majority of respondents answered at the level of reality and expectations were agreed and strongly agreed. The discrepancy or gap values ​​between expectations and reality are: reliability dimension (-0.95); responsiveness (-0.91); assurance (-0.62); empathy (-0.63); and tangibles (-0.72). Meanwhile, the satisfaction scores of outpatient polyclinic officers with the service of providing outpatient medical records based on the CSI (Customer Satisfaction Index) method are: reliability dimension (76.18%); responsiveness (77.81%); assurance (79.84%); empathy (80.86%); and tangibles (78.20%). The general description of the performance of outpatient medical record services can be said to be good. The gap value for all dimensions of service quality is negative. The level of satisfaction of outpatient polyclinic officers with the provision of outpatient medical records services for the five dimensions of service quality based on the CSI (Customer Satisfaction Index) method is interpreted as being all satisfied.